Optimizing Variable Step-Size Least Mean Square Using Support Vector Machine for Motion Artifact Reduction - MOHD ZAILAN, KHALIDA ADEEBA (2021)
“Over the past decades, the significance advancement in wearable sensor technology has been a well-known technology in medical sector especially for health monitoring device.